Cultural factors and the circadian rhythm of ST elevation myocardial infarction in patients in a Mediterranean island - Protopapas, Andreas; Lambrinou, Ekaterini (My University, 2019)
Introduction: The circadian rhythm of onset of myocardial infarction shows an increased risk during the morning hours. However, it is not clear whether habits, culture and sunshine hours differentiate circadian rhythm. The aim of this study was to investigate the influence of cultural factors on the circadian rhythm of acute myocardial infarction with ST segment elevation in a Mediterranean island. Method: The study was a retrospective correlational survey. It included 123 patients with ST elevation myocardial infarction (mean age 60.7±12.6; 82% men). The 24 h of a day were divided into four six-hour periods of time for study purposes (00:01–06:00; 06:01–12:00; 12:01–18:00; and 18:01–24:00) and the chi-square test was used for the analysis. Results: A morning peak of symptoms onset of ST-elevation myocardial infarction was detected during the period 06:01–12:00 (p=0.044). In patients who were smokers, a bimodal pattern involving a morning (06:01–12:00) and an afternoon-to-night peak (18:01–24:00) (p=0.005) was detected. For patients with a history of hypertension, a morning peak of their symptoms was also detected (p=0.028). Different circadian variations were found between patients over the age of 60 years old and patients under the age of 60 years old (p=0.025). Conclusions: Patients with ST elevation myocardial infarction seem to follow a circadian rhythm with a peak of onset of symptoms in the morning. In the smokers’ subgroup, a different circadian pattern was found. The habit of smoking is likely to affect the circadian rhythm of the onset of ST elevation myocardial infarction in the Mediterranean area and culture.
Keywords: Circadian rhythm; Mediterranean; Myocardial infarction